2018
DOI: 10.1093/nar/gky494
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary rates of mammalian telomere-stability genes correlate with karyotype features and female germline expression

Abstract: Telomeres protect the ends of eukaryotic chromosomes and are essential for cell viability. In mammals, telomere dynamics vary with life history traits (e.g. body mass and longevity), suggesting differential selection depending on physiological characteristics. Telomeres, in analogy to centromeric regions, also represent candidate meiotic drivers and subtelomeric DNA evolves rapidly. We analyzed the evolutionary history of mammalian genes implicated in telomere homeostasis (TEL genes). We detected widespread po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…For example, human centromeric dimeric arrays might be expanding due to their more efficient recruitment of centromeric protein shown by centromeric chromatin profiling [ 49 , 196 , 200 , 203 ]. Analogous to centromeric satellites, subtelomeric satellites of different organisms show no sequence similarity and have been proposed to be subjected to telomere drive in which rapid sequence changes in the subtelomeric DNA can trigger adaptation of telomeric proteins to restore telomere homeostasis [ 305 , 306 , 307 ].…”
Section: Satellite Evolutionmentioning
confidence: 99%
“…For example, human centromeric dimeric arrays might be expanding due to their more efficient recruitment of centromeric protein shown by centromeric chromatin profiling [ 49 , 196 , 200 , 203 ]. Analogous to centromeric satellites, subtelomeric satellites of different organisms show no sequence similarity and have been proposed to be subjected to telomere drive in which rapid sequence changes in the subtelomeric DNA can trigger adaptation of telomeric proteins to restore telomere homeostasis [ 305 , 306 , 307 ].…”
Section: Satellite Evolutionmentioning
confidence: 99%
“…Furthermore, longer telomeres may be needed to protect longer chromosomes from end denaturation and rearrangements (Pampalona, Soler, Genescà, & Tusell, 2010; Slijepcevic, 1998). Supporting the connection between TL and chromosome size, Pontremoli et al (2018) found that positive selection on genes implicated in telomere homeostasis among mammals was related to the number of chromosome arms. Given that genome size is relatively conserved among mammals (Kapusta et al, 2017), the positive selection at these genes is likely driven by chromosome size and these genes might help calibrate specific telomeres to the corresponding chromosomes.…”
Section: Discussionmentioning
confidence: 86%
“…Using large phylogenies of mammalian orthologues (Table ), we calculated the dN/dS parameter (Kosakovsky Pond & Frost, 2005; Table ). In particular, we compared the distribution of dN/dS for this centromere gene set to the one previously calculated for genes encoding CENP‐A and proteins involved in CENP‐A deposition (10 genes; Pontremoli et al, 2018). As a comparison, genes involved in telomere homeostasis (TEL genes), which have also been involved in an intragenomic genetic conflict, as well as a set of random genes were analysed (Pontremoli et al, 2018; Figure 2; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…“Textmining,” “Experiments” and “Databases” string active interaction sources were selected. Proteins are coloured according to the observed selection pattern, either described herein or in a previous work (Pontremoli et al, 2018). The percentage of sites evolving with dN/dS > 1 was obtained from the codeml M8 model.…”
Section: Resultsmentioning
confidence: 99%